WhatsApp blast as digital multiliteracy 4.0 product to improve students’ English learning achievement - Permadi, Rudi; Munir, Asep Ahmad Arsyul (Research and Social Study Institute, 2024)
The research was carried out to recognize the influence of WhatsApp Blast on the students’ English learning achievement. Experiment with one group pre-test and post-test factorial design was played as a research methodology. Multiple choice test ruled data collection. The number of samples was 120 students taken from three private universities. Random sampling works as a technique for taking the sample. Data calculation and analysis concluded that Asymp. Sig. (2-tailed) =0.000 less than Asymp. Sig. (2-tailed) < 0.05 explaining that H0 is rejected. The result is also strengthened by the fact that the mean average score after treatment is higher than before treatment. The average mean score of the pre-test is 48.7, and the average mean score of the post-test is 67.1. It means that WhatsApp Blast significantly affected the student’s English learning achievement. The next research should take a larger population and sample.